Long term safety of sacral nerve modulation in medicare beneficiaries. Issue 7 (25th July 2014) - Chughtai, Bilal; Sedrakyan, Art; Isaacs, Abby; Lee, Richard; Te, Alexis; Kaplan, Steven
<x xml:space="preserve">Abstract</x> Aims Sacral nerve stimulation (SNS) is FDA approved as second‐line therapy for both urinary and bowel control. However, there is limited evidence regarding long term safety. We determined adverse events associated with SNS among Medicare beneficiaries. Methods We used the 5% national random sample of Medicare claims for 2001–2011 to identify patients. Patients who underwent SNS implantation were identified with Current Procedure Terminology (CPT‐4) codes. We determined safety of SNS using analysis of complication occurrences on day of surgery and during 5 years following initial procedure. SAS v9.3 statistical package was used. Results One thousand four hundred seventy‐four patients underwent treatment with SNS in the 5% national sample of Medicare patients within the time period. Representative of real‐world patients undergoing SNS surgery, comorbidities included hypertension (69.3%), diabetes (29.4%), chronic pulmonary disease (25.5%), hypothyroidism (25.2%), and depression (22.7%). Few complications occurred on day of surgery. At 90 days, 3.2% of patients had bowel complications, 2.0% urological, 9.4% infectious, and 1.5% stroke. Overall, bowel, neurological health event occurrences were consistent with prior year rates, while infectious events decreased. Of 206 patients who were followed for at least 5 years, 17.3% had devices removed and 11.3% replaced, with 26.1% having at least one of those, leaving 73.9% with original devices. Conclusions Urological, infectious, and bowel complication occurrences were low after SNS among Medicare beneficiaries with multiple comorbidities. There were infrequent serious complications like hemorrhage and stroke postoperatively. Although SNS appears safe in this high‐risk population, a comprehensive registry will ensure continuous safety. Neurourol. Urodynam. 34:???–???, 2015. © 2014 Wiley Periodicals, Inc.